Trust in political institutions as a resource of reputation capital of the state - Vladimirovich Tolochko, Aleksandr (2019)
The issue of the effectiveness of the state’s reputation capital in Russian political system is being studied in the context of its matter, structure, organization factors, trends, approaches and patterns.The subject of the study is the trust in the main political institutions as a resource of reputation capital of the state.The following Russian and foreign scientists devoted their works to the study of the reputation capital and its trust: Anokhin, Byba, Grankin, Rozanova, Rudakova, Timofeeva, Baudrillard, Bourdieu, Toffler, and Fukuyama.The purpose of the study is to analyze Russian reputation capital in the context of turbulence, increasing global instability, new challenges, risks and threats. The researchers tend to solve the following tasks: to determine the essence of the state’s reputation capital; to reveal the level of the state’s reputation through the level of trust in its political institutions; to identify trends of its strengthening and weakening in the context of trust.The authors applied the following studying approaches and methods: systemic, institutional, neoinstitutional and comparative approaches; comparative analysis, structural and functional analysis, sociological analysis, observation, overt observation and extrapolation.In the article, the essence of the state’s reputation capital is considered. The components of its structure are studied. Aspects of disappointment with the functioning of some classical political institutions are highlighted.The results of the study are in demand when making political decisions in the context of national security, effective social policy transformation into the basic mechanism of power legitimization, development of moral and ethical requirements for modern politics, creation and implementation of programs and images for political actors.The establishment and development of new growth points in Russia is impossible without the increasing of the trust in the state and its political institutions, without building up its reputation capital, ensuring civil peace and harmony.